Achievable diversity orders of decode-and-forward cooperative protocols over gamma-gamma fading FSO links - Abou-Rjeily, Chadi (2013)
In this paper, we consider the problem of relay-assisted free-space optical (FSO) transmissions with any number of relays. At a first time, we consider the quantum limited scenario and analyze the simple Decode-and-Forward (SDF) protocol where all symbols received at a certain relay are retransmitted to the destination. We also propose a novel Selective-DF (SelDF) protocol that can be implemented without requiring any kind of channel state information (CSI) neither at the transmitter nor at the receiver sides. We derive the diversity orders that can be achieved by SDF and SelDF over gamma-gamma fading channels and highlight the superiority of SelDF. We also prove that for some network configurations, SDF might achieve the same diversity order as SelDF. On the other hand, for most of the network configurations, the SDF protocol, that was studied extensively in the context of N_r-relays radio-frequency (RF) systems and one-relay FSO systems, is not suitable for FSO systems with more than one relay since it results in reduced diversity orders. At a second time, the above protocols are extended to FSO systems that are corrupted by background radiation. For SelDF, we propose a novel metric that captures the fidelity with which a certain message is detected at the relay thus determining whether this relay will participate in the cooperation effort or not.